Pemetaan Spasial Kasus HIV/AIDS dan Aksesibilitas Pelayanan Kesehatan di Kota Surakarta Berbasis QGIS - Mayasari, Ovita; Naury, Chairullah; Fiesta, Cheelsy Arsa (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
The number of newly detected HIV/AIDS cases in Surakarta City has increased annually, with 425 cases reported in 2022, 453 in 2023, and 323 cases recorded up to August 2024. This study aimed to map the spatial distribution of HIV/AIDS cases to identify high-risk transmission areas, analyse spatial patterns and trends, and support more effective planning and evaluation of HIV programmes. Using a descriptive ecological design, the study employed secondary data from the Surakarta City Health Office and local AIDS-focused NGOs. Spatial analysis was conducted using overlay and buffering techniques in QGIS. The results showed varying case distributions across sub-districts, represented by colour gradients from dark red (highest case numbers) to white (lowest). Health service availability includes seven hospitals and seventeen primary health centres providing HIV testing, while 107 hotspot areas were identified among key populations, including MSM, transgender individuals, female sex workers, and people who inject drugs. Health service coverage was found to be evenly distributed across all sub-districts. The study recommends that the Health Office and AIDS-related NGOs continue spatial mapping efforts to better identify high-risk transmission areas and strengthen HIV prevention strategies in Surakarta City.